Mortality of workers exposed to styrene in the manufacture of glass-reinforced plastics. - Coggon, David; Osmond, C; Pannett, Brian; Simmonds, S; Winter, Paul D; Acheson, E D (Scandinavian Journal of Work, Environment & Health, 1987)
Epidemiologic studies have suggested an increased risk of leukemia and lymphoma among workers exposed to styrene. In a further exploration of this possible hazard, an analysis was conducted of the mortality among 7,949 men and women employed during 1947-1984 in eight British companies manufacturing glass-reinforced plastics. The subjects were identified from company files and traced to the end of 1984 through National Health Service and National Insurance records. The overall mortality in the cohort was less than in the national population (693 deaths observed, 830.1 expected) as was mortality from cancer (181 deaths observed, 223.7 expected). In particular, there was a deficit of deaths from lymphoid and hemopoietic cancer (6 observed, 14.9 expected). The small excess of lung cancer (89 deaths observed, 80.1 expected) was not statistically significant and can probably be attributed to chance. Among 3,494 hand laminators (the job with the highest exposure to styrene) there was one death from lymphoma and none from leukemia. The findings do not exclude the possibility that styrene is a human carcinogen, but give no support to the hypothesis that it causes leukemia and lymphoma.